A conventional reading applicable to first instance decisions in the matter of protection - Castañeda Méndez, Juan Alberto (2020)
The purpose of this work is to make a specific decision regarding the convening use used by the judge of first instance when ruling cases in constitutional matters (10 sentences of amparo process). For this purpose, a journey of main ideas is made about internally headquartered conventionality and its expressions of judicial use.